Fish Protein Hydrolysates: Bioactive Properties, Encapsulation and New Technologies for Enhancing Peptides Bioavailability - Moya Moreira, Thaysa F.; Gonçalves, Odinei Hess; Leimann, Fernanda Vitória; Ribeiro, Ricardo Pereira (Current Pharmaceutical Design, 2023)
Fish protein hydrolysates (FPHs) can be obtained from substrates such as fish muscle, skin, and wastes and assign value to these fish by-products. Proteolytic enzymes catalyze the hydrolysis of these fish substrates' peptide bonds resulting in smaller peptides that present several bioactive properties. Hydrolysates' bioactive properties are a function of the fish species used as the substrate, the enzyme selectivity or specificity, pH and temperature applied in the reaction, etc. Furthermore, many pre-treatment methods are being applied to fish protein substrates to improve their enzyme susceptibility and increase the number of smaller bioactive peptides. This review addresses the production of FPHs and the main bioactive properties evaluated recently in the literature and emphasizes the substrate treatments by high-pressure processing, microwave, ultrasound, and thermal treatments to achieve better bioactivity making essential amino acids more available in peptides. The bioactive properties most found in FPHs were antioxidants, antimicrobials, anticancer, and antihypertensive. These bioactivities may vary depending on the conditions of hydrolysis, fish species, and fractionation and isolation of specific peptides.New technologies for the treatment of by-products can reduce process losses and achieve better results by cleavage of proteins. Conversely, encapsulation and film utilization can improve bioactivity, bioavailability, and controlled release when applied to foods, resulting in improved health.
Keywords: new technologies